Detection and Replication of Moku Virus in Honey Bees and Social Wasps - Andrea Highfield (Viruses, 2020)
Transmission of honey bee viruses to other insects, and vice versa, has previously been reported and the true ecological importance of this phenomenon is still being realized. Members of the family Vespidae interact with honey bees via predation or through the robbing of brood or honey from colonies, and these activities could result in virus transfer. In this study we screened Vespa velutina and Vespa crabro collected from Europe and China and also honey bees and Vespula vulgaris from the UK for Moku virus (MV), an Iflavirus first discovered in the predatory social wasp Vespula pensylvanica in Hawaii. MV was found in 71% of Vespula vulgaris screened and was also detected in UK Vespa crabro. Only seven percent of Vespa velutina individuals screened were MV-positive and these were exclusively samples from Jersey. Of 69 honey bee colonies screened, 43% tested positive for MV. MV replication was confirmed in Apis mellifera and Vespidae species, being most frequently detected in Vespula vulgaris. MV sequences from the UK were most similar to MV from Vespula pensylvanica compared to MV from Vespa velutina in Belgium. The implications of the transfer of viruses between the Vespidae and honey bees are discussed.